Pharmacotherapy And Behavioural-Modifying-Lifestyle For Oral Lesions Management In Multimorbid Patient Post-Pyelolithotomy: A Case Report - Selviana Rizky Pramitha; Arissa Izzati; Maharani Laillyza Apriasari; Amy Nindia Carabelly; Dewi Puspitasari (Odonto : Dental Journal, 2026)
Background: Chronic kidney disease (CKD), a recognized complication of pyelolithotomy along with multimorbidity in the elderly population, presents a higher incidence of oral lesions. Further damage to the renal vasculature interchangeably affects oral-systemic conditions. We report oral lesions management in MCC patient post-pyelolithotomy for better outcomes.  Case: A 65-year-old male patient complained of painful ulceration on the atrophic tongue for two weeks with a fair oral hygiene score. The condition had been managed with various topical agents alternately with no improvement. There was a history of pyelolithotomy and emergency room admission. Laboratory examination presented diabetes mellitus, stage 3B kidney disease and anemia of chronic disease. A diagnosis of ulcerative-type uremic stomatitis with atrophic glossitis in multimorbid patient was obtained. Pharmacotherapy of oral lesion including aloe vera extract mouthwash and povidone-iodine mouthwash showed improvement on the following day. Behavioural-modifying lifestyle involved physical activity, healthy eating, and adherence to treatment (oral hygiene maintenance and regular dental appointment). Systemic conditions were managed by multidiscipline treatment with Internal Medicine. Conclusion: Pharmacotherapy and behavioral modifying lifestyle may support a better prognosis for oral manifestation in multimorbid patient post pyelolithotomy